2015
DOI: 10.1007/s12600-015-0480-3
|View full text |Cite
|
Sign up to set email alerts
|

First report of the Sub-Saharan Africa 2 species of the Bemisia tabaci complex in the Southern France

Abstract: An extensive survey was conducted in the major crop producing regions of France, Spain, Greece, Tunisia and Morocco from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Genetic diversity estimates indicated that this population had lower allelic richness compared to other African populations, which suggests that a subset of the source population was introduced and survived in the sampled area, likely undergoing a genetic bottleneck. Although this biotype had only been previously reported in Spain outside its African native range, a recent study also reported its presence in Southern France [125]. In that study, it was shown that microsatellite genotypes from individuals originating from a French Q biotype (Western Mediterranean) sample were not clearly assigned to the biotype S population, but seemed to have admixed ancestry between the Q and S biotypes.…”
Section: Discussionmentioning
confidence: 90%
“…Genetic diversity estimates indicated that this population had lower allelic richness compared to other African populations, which suggests that a subset of the source population was introduced and survived in the sampled area, likely undergoing a genetic bottleneck. Although this biotype had only been previously reported in Spain outside its African native range, a recent study also reported its presence in Southern France [125]. In that study, it was shown that microsatellite genotypes from individuals originating from a French Q biotype (Western Mediterranean) sample were not clearly assigned to the biotype S population, but seemed to have admixed ancestry between the Q and S biotypes.…”
Section: Discussionmentioning
confidence: 90%
“…SSA-CA is a clear example of how mtCOI provides a misleading indication of genetic identity, since all of these individuals were identified as SSA1-SG1 with mtCOI, despite the fact that they have higher proportions of shared genetic identity with SSA4 and SSA-ESA. SSA2 individuals in this study were all from Cameroon, although SSA2 individuals identified using mtCOI have been found in countries as distantly separated as Uganda in East Africa ( Legg et al 2002 ; Mugerwa et al 2012 ), and Spain and France in southern Europe ( Hadjistylli et al 2015 ). In view of the inconsistencies in the genotyping results obtained using the mtCOI and SNP methods in this study, it seems likely that SSA2 populations identified from different regions/countries using mtCOI may be genetically quite distinct.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the endemic African cassava Bemisia whitefly SSA2 species occupies regions affected by the CMD pandemic. SSSA2 has also expanded into southern Europe since 2007 20 whereas SSA1 has not (though widespread throughout the African continent). Defining the actual CMD vectors in Africa remains a challenge due to the cryptic nature of the many species in the Aleyrodidae whitefly genus Bemisia 3 , 18 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%